Chemical, nutritive, fermentative and microbial composition of almond hull silage - Selim Sırakaya (Journal of Applied Animal Research, 2023)
Almond hulls are generally used as feed after drying. In this study, silage was made from almond hulls and quality and feed potential were investigated. In this context, chemical, fermentation, microbiological analyses and digestion–energy calculations were made. The total weight of the almond fruit was 10.47 ± 1.68 g, the hull weight was 6.56 ± 1.30 g and the percentage of the hull to the total fruit was 62.48 ± 6.57. In the almond hull silage samples, pH 5.75 ± 0.01, NH3–N 112.5 ± 1.45 g kg−1, lactic acid 63.79 ± 1.83 g kg−1, acetic acid 22.94 ± 1.93 g kg−1, propionic acid 28.27 ± 1.45 g kg−1 and butyric acid 9.59 ± 0.88 g kg−1 were determined. Yeast–mould and enterobacter were not detected and the lactic acid bacteria was 4.54 ± 0.04 log cfu g−1. The most potassium 1212.50 ± 23.90 ppm, calcium 621.36 ± 23.91 ppm and magnesium 586.25 ± 21.43 ppm minerals were found. Crude protein was 92.5 ± 5.9 g kg−1, crude ash 111.3 ± 1.1 g kg−1, acid detergent fibre 282.7 ± 2.9 g kg−1, neutral detergent fibre 394.3 ± 2.7 g kg−1, total digestible nutrients 521.7 ± 8.5 g kg−1, metabolic energy 1.85 ± 0.03 mcal kg−1 and net energy lactation 1.11 ± 0.03 mcal kg−1 were determined. It was concluded that although almond hull fermentation properties are partially desirable, they can be stored and used as silage.